Food Critics, Food and Society in Hong Kong - Hom, Ken (Petits Propos Culinaires, 2024)
Ken Hom, author of Chinese Technique (Simon and Schuster, New York, 1981) frequently visits Hong Kong. Here he gives impressions formed during some recent visits, and a couple of shrimp (prawn) recipes which he particularly recommends.